National Cancer Control Plan of the Korea: Current Status and the Fourth Plan (2021-2025) - Kyu-Tae Han; Jae Kwan Jun; Jeong-Soo Im (Korean Society for Preventive Medicine, 2023)
Cancer management has become a major policy goal for the government of the Korea. As such, the government introduced the National Cancer Control Plan (NCCP) to reduce the individual and social burdens caused by cancer and to promote national health. During the past 25 years, 3 phases of the NCCP have been completed. During this time, the NCCP has changed significantly in all aspects of cancer control from prevention to survival. The targets for cancer control are increasing, and although some blind spots remain, new demands are emerging. The government initiated the fourth NCCP in March 2021, with the vision of "A Healthy Country with No Concerns about Cancer Anywhere at Any Time," which aims to build and disseminate high-quality cancer data, reduce preventable cancer cases, and reduce gaps in cancer control. Its main strategies include (1) activation of cancer big data, (2) advancement of cancer prevention and screening, (3) improvement in cancer treatment and response, and (4) establishment of a foundation for balanced cancer control. The fourth NCCP has many positive expectations, similar to the last 3 plans; however, cross-domain support and participation are required to achieve positive results in cancer control. Notably, cancer remains the leading cause of death despite decades of management efforts and should continue to be managed carefully from a national perspective.